The impact of active social media use on the mental health of older adults - Ning Wei; Dingqiang Sun; Jian Li (BMC Psychology)
Abstract Background With the rising population age and the development of information technology in China, a growing number of older adults use social media as a means of social participation. The impact of posting on WeChat Moments on the mental health of older adults is worthy of attention. Aim The aim of this study is to identify posting on WeChat Moments as an active social media use and analyze its impact on the mental health of older adults. Method Using the survey data from the China Health and Retirement Longitudinal Study (CHARLS), we defined posting on WeChat Moments as an active social media use and used propensity score matching (PSM) to analyze the impact of such posting on the mental health of older adults. Results The results of the study showed that posting statistically significantly improved the depression, self-rated health, and health satisfaction of older adults. Heterogeneity analysis showed that the female older-adult population and the younger older-adult population derived the most mental health benefit from posting on WeChat Moments. Conclusion Posting on WeChat Moments statistically significantly improved the depression, self-rated health, and health satisfaction of older adults. Older adults who use WeChat and post on WeChat Moments derive much benefit from their active social media use.